The views of women and pharmacists on the desirability of a progestogen-only pill over the counter. Results of a survey in Germany, Italy and Spain. (2nd November 2022) - Arisi, Emilio; Bauer, Cosima; Farris, Manuela; Giulini-Limbach, Chiara; Glasier, Anna; Lete, Inaki; May, Uwe; Mirjalili, Noushin; Nappi, Rossella E.; Sanchez-Borrego, Rafael; Serrano, Isabel
Abstract: Purpose: To explore the perceived need and enthusiasm for over the counter (OTC) progestogen-only pills (POP). Materials and Methods: A web-based survey of 1000 sexually active women (16–45) and 100 pharmacists in Germany, Italy and Spain. Results: Despite not wanting to conceive, 5–6% of women in each country were not using contraception and 8–20% were using methods less effective than condoms. At least 74% of respondents felt knowledgeable about the different contraceptives available but at least 1/3 had experienced difficulty accessing oral contraceptive (OCs) in the past two years. The cost of contraceptives, the need to see a doctor and long waits for appointments were cited as barriers for not using OCs. The majority agreed they would discuss with their doctor the decision to buy the POP, consult about side effects and other reproductive health issues. Over 2/3 of pharmacists in each country would be very, or fairly, likely to recommend the POP, agreeing that the benefits included improved access for women, and offered them more independence. Conclusions: Asked directly, women in Germany, Spain and Italy currently using contraception are positive about a POP OTC. Pharmacists are also positive, with the overwhelming majority in favour of providing POPs.